2023
DOI: 10.1038/s41598-023-32783-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between food desert severity, socioeconomic status, and metabolic state during pregnancy in a prospective longitudinal cohort

Abstract: Poor metabolic health during pregnancy is associated with health concerns for pregnant individuals and their offspring. Lower socioeconomic status (SES) is one risk factor for poor metabolic health, and may be related to limited access to healthful and affordable foods (e.g., living in a food desert). This study evaluates the respective contributions of SES and food desert severity on metabolic health during pregnancy. The food desert severity of 302 pregnant individuals was determined using the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Within our fully adjusted analysis, we determined that residing in a USDA-designated food desert increased the likelihood of preterm birth in a dose-response manner. Our results were consistent with existing studies that linked inadequate access to healthy foods to poor maternal health and birth outcomes [9,31,32]. Furthermore, residing in a food desert has been associated with health implications beyond conception health and birthing outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Within our fully adjusted analysis, we determined that residing in a USDA-designated food desert increased the likelihood of preterm birth in a dose-response manner. Our results were consistent with existing studies that linked inadequate access to healthy foods to poor maternal health and birth outcomes [9,31,32]. Furthermore, residing in a food desert has been associated with health implications beyond conception health and birthing outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…2 ). However, other studies have reported that a lack of access to healthy foods can mediate the relationship between lower SES and higher body fat during pregnancy, 37 and that lower neighborhood-level SES was associated with reduced vegetable consumption. 38 Thus, research in other settings is warranted to determine if SES disparities exist in the relationship between the food environment the odds of having GDM among pregnant individuals.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, only a few studies discuss food choice and linkages to food apartheid, food deserts, or food inequities and their impact on pregnant Black women [8,23,[34][35][36]. These studies reported that built food environments are significantly associated with pregnancy morbidity [34,36] and impede food choice [35]. Specifically for Black women, Reyes et al (2013) examined motivators and barriers to healthy eating in 21 overweight Black pregnant women in Philadelphia [8].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few studies discuss food choice and linkages to food apartheid, food deserts, or food inequities and their impact on pregnant Black women [ 8 , 23 , 34 , 35 , 36 ]. These studies reported that built food environments are significantly associated with pregnancy morbidity [ 34 , 36 ] and impede food choice [ 35 ].…”
Section: Discussionmentioning
confidence: 99%